LEGAL ASPECTS OF BANKRUPTCY PEACE THROUGH RESTRUCTURING CORPORATE DEBT IN THE DIGITAL ECONOMY ERA - Ida Nadirah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The digital economy era has brought significant transformations in the business world, including in the aspect of corporate debt management. In the context of bankruptcy, the traditional approach that tends to focus on the liquidation of corporate assets has begun to be replaced by the peace model through debt restructuring. This approach aims to provide an opportunity for companies experiencing financial difficulties to recover and contribute to the economy. This study aims to analyze the legal aspects of bankruptcy peace through corporate debt restructuring, especially in the digital economy era. The main focus is to identify the applicable legal framework, challenges faced, and opportunities offered by digital technology in the debt restructuring process. The research method used is normative juridical with a conceptual approach and analysis of relevant regulations, including the Bankruptcy and Suspension of Debt Payment Obligations Law (PKPU) in Indonesia. The results of the study indicate that the peace mechanism through debt restructuring has great potential to increase the efficiency and effectiveness of bankruptcy dispute resolution. In the digital era, technologies such as blockchain and digital platforms can be used to increase transparency, accountability, and speed of the restructuring process. However, the implementation of this technology faces challenges, including a lack of specific regulations, data security risks, and resistance from traditional stakeholders.